2011
DOI: 10.1371/journal.pone.0023503
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Salivary Bacterial Microbiome Diversity in Edentulous Infants and Their Mothers or Primary Care Givers Using Pyrosequencing

Abstract: Bacterial contribution to oral disease has been studied in young children, but there is a lack of data addressing the developmental perspective in edentulous infants. Our primary objectives were to use pyrosequencing to phylogenetically characterize the salivary bacterial microbiome of edentulous infants and to make comparisons against their mothers. Saliva samples were collected from 5 edentulous infants (mean age = 4.6±1.2 mo old) and their mothers or primary care givers (mean age = 30.8±9.5 y old). Salivary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
141
3
10

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(182 citation statements)
references
References 37 publications
28
141
3
10
Order By: Relevance
“…It is therefore conceivable that the observed microbiota changes in posttransplant compared to pretransplant samples are reflective of an improved health state as patients stabilize or recover organ function after transplantation. However, since antimicrobial therapy is part of the standard posttransplant regimen, the observed changes could also result from these medications, which would be supported by the observation that all of the bacterial groups showing decreases in relative abundance are also found at relatively high numbers in healthy patients, including, for example, Haemophilus and Neisseria species in the oral microbiota (27).…”
Section: Discussionmentioning
confidence: 92%
“…It is therefore conceivable that the observed microbiota changes in posttransplant compared to pretransplant samples are reflective of an improved health state as patients stabilize or recover organ function after transplantation. However, since antimicrobial therapy is part of the standard posttransplant regimen, the observed changes could also result from these medications, which would be supported by the observation that all of the bacterial groups showing decreases in relative abundance are also found at relatively high numbers in healthy patients, including, for example, Haemophilus and Neisseria species in the oral microbiota (27).…”
Section: Discussionmentioning
confidence: 92%
“…Leptotrichia species were also isolated from bronchoalveolar lavage fluid, and patients with leukocytosis, hypoxemia, and dyspnea [24]. Further, Leptotrichia species were recovered from healthy patients with oral cancer, premalignant oral lesion [18,28,33,56,91], edentulous infants [29], human vaginal fluid of sexually active and inactive individuals [30,32], HIV-seropositive and -seronegative patients [46], pancreatic cancer patients [18,66], black pigmented stain caries patients [63], and patients with halitosis (Table 2) [42,65,81,82]. Besides, Leptotrichia species were isolated from the blood [4,5,22,74], the amniotic fluid of a patient with a wound and respiratory difficulties [4], breast milk of obese women with gestational diabetes and normal weight [36], oral samples of a patient with new-onset rheumatoid arthritis [20], oral lichen planus patients [88], and even from fermenting Lees liquor [39].…”
Section: Brief Additional Clinical Information On Leptotrichia Speciesmentioning
confidence: 99%
“…A more recent study using NGS also observed the same trend; saliva samples were collected from five oedentulous infants aged 3-6 months and their mothers or primary carers. More than 200 genera were identified in infants, with Neisseria being one of the predominant genera (Cephas et al, 2011). In addition to the oral cavity, the composition of the nasopharyngeal microbiome has been investigated by barcoding pyrosequencing in 96 healthy children of 18 months of age (Bogaert et al, 2011).…”
Section: Neisseria: a Significant Component Of The Human Microbiomementioning
confidence: 99%